Growth, Yield and Profitability of Cabbage (Brassica oleracea L.) as Influenced by Applied Nitrogen and Plant Spacing (The Agriculturists, 2016)
An experiment was conducted with cabbage during October 2012 to February 2013 at the Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh. Four levels of nitrogen: viz. 0, 150, 250 and 350 kg ha-1 and three plant spacings: 50 x 30, 50 x 40 and 50 x 50 cm were applied in a Randomized Complete Block Design with three replications. Nitrogen @ 250 kg ha-1 with the spacing of 50 x 50 cm was more effective and produced the highest fresh weight of head(2.17 kg), marketable head yield (86.93 t ha-1). This treatment was also more profitable than the rest of the treatments, while the lowest profit was in N0S1.The Agriculturists 2015; 13(1) 35-45